FLUVIO-DELTAIC DEPOSITIONAL COMPLEX OF THE CAMPANO-MAASTRICHTIAN GOMBE FORMATION OF THE GONGOLA SUB-BASIN, NORTHERN BENUE TROUGH, N.E. NIGERIA - Shettima, Bukar; Bukar, Mohammed; Adams, Fatimoh Dupe (International Journal of Research -GRANTHAALAYAH, 2020)
Evaluation of the stratigraphic architecture of the Gombe Formation of the Gongola Sub-basin in the Northern Benue Trough indicated a build-up from six facies assemblage that consist of trough crossbedded sandstone, planar crossbedded sandstone, massive bedded sandstone, ripple laminated sandstone, parallel laminated sandstone and mudstones. These units were packaged into three facies association that constitutes of bedded sandstone facies association (FAgI), interbedded sandstone and mudstone facies association (FAgII) and amalgamated trough crossbedded sandstone facies association (FAgIII). These reflects mouth-bars, pro-delta and delta slope deposits and upper delta plain respectively. This deltaic prism is characterized by unidirectional current system devoid of signatures of tide and waves hydrodynamics in the subaqueous delta regions, thus indicating that the delta system of the Gombe Formation is a fluvial dominated delta.